Investigation on the Efficacy of a Killed Salmonella pullorum Vaccine (Microbes and Health, 2013)
This study was carried out to determine the efficacy of a formalin-killed alum-precipitated Salmonella pullorum vaccine prepared by the Livestock and Poultry Vaccine Research and Production Centre (LPVRPC), BAU, Mymensingh, Bangladesh. Immunization with this vaccine induced serum antibody titers that peaked in 2-week following both primary and booster vaccination (P